Effects of riluzole on spinal seizure-like activity in the brainstem-spinal cord preparation of newborn rat. (December 2017) - Lin, Shih Tien; Ohbayashi, Masayuki; Yamamoto, Toshinori; Onimaru, Hiroshi; Kogo, Mari
Highlights: Riluzole is known as a persistent sodium channel blocker. We examined the effects of riluzole on seizure-like activity in newborn rat in vitro. Seizure-like activity was induced by application of TBOA or bicuculline/strychnine. Riluzole depressed drug-induced seizure-like activities without respiratory suppression. Riluzole can potentially protect against drug-induced epileptic brain tissue damage. Abstract: Riluzole blocks persistent Na + current, inhibits generation of neuronal bursts and decreases glutamate-induced excitotoxicity. In previous studies of respiratory activity, riluzole suppressed inspiratory-related burst generation activity in rat slice or en bloc preparations. We examined riluzole's effects on inspiratory burst generation and drug-induced seizure-like activity in newborn rat en bloc preparations. Medulla-spinal cord preparations from postnatal day 0–3 Wistar rats were isolated under deep isoflurane anesthesia and were superfused with artificial cerebrospinal fluid equilibrated with 95% O2 and 5% CO2, pH 7.4, at 25–26 °C. Inspiratory activity was monitored from the fourth cervical ventral root. Seizure-like activity was induced by application of 20 μM DL- threo -β-benzyloxyasparatate (TBOA, a glutamate uptake blocker preferentially acting on astrocytes) or coadministration of GABAA antagonist bicuculline (10 μM) and glycine antagonist strychnine (10 μM). Pretreatment and co-application with 10 μM riluzole abolished the seizure-like burst activity induced by TBOA or bicuculline/strychnine. N -methyl-d -aspartic acid receptor antagonist MK801 (10 μM) also depressed this activity. Riluzole may attenuate excessive glutamate action involved in pathological hyperexcitability of motor neurons with no major effect on generation of respiratory activity. Riluzole at the optimal dose could be a potential treatment to protect drug-induced epileptic brain tissue from excitotoxic damage without inducing respiratory suppression.